2022
DOI: 10.1186/s43042-022-00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and diagnostic values of MIAT, H19, and NRON long non-coding RNAs in multiple sclerosis patients

Abstract: Background Multiple sclerosis (MS) is a chronic inflammatory disease. Various long non-coding RNAs (lncRNAs) appear to have an important role in the pathophysiology of MS. This study aimed at evaluating the expression levels of lncRNAs, MIAT, H19, and NRON in peripheral blood of MS cases to a healthy control group. We collected blood samples of 95 MS cases (76 relapsing–remitting (RR) and 19 secondary progressive (SP) MS) and 95 controls. We used quantitative real-time PCR for the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…However, some studies suggest that lncRNA H19 is implicated in CNS diseases through the JAK/STAT pathway and the activation and proliferation of astrocytes and microglia (30). Consistent with our fi ndings, Amiri et al found that the expression of lncRNA H19 is signifi cantly higher in SPMS and RRMS subgroups compared to healthy individuals (31). However, in the study by Meber et al, it was reported that the serum levels of lncRNA H19 in MS patients were lower than in healthy subjects (27).…”
Section: Discussionsupporting
confidence: 90%
“…However, some studies suggest that lncRNA H19 is implicated in CNS diseases through the JAK/STAT pathway and the activation and proliferation of astrocytes and microglia (30). Consistent with our fi ndings, Amiri et al found that the expression of lncRNA H19 is signifi cantly higher in SPMS and RRMS subgroups compared to healthy individuals (31). However, in the study by Meber et al, it was reported that the serum levels of lncRNA H19 in MS patients were lower than in healthy subjects (27).…”
Section: Discussionsupporting
confidence: 90%
“…Previous results con rmed the in ammatory effect of MIAT up-regulation with a positive correlation with disease severity in IS [38,39], coronary artery disease [40], multiple sclerosis [41], and cancer [42]. The in ammatory mechanisms of MIAT has been suggested to participate in endothelial in ammation, vascular dysfunction [43], vascular leakage and upregulation of IL-1β and IL-6 [44].…”
Section: Discussionmentioning
confidence: 79%
“…Subsequent careful screening of abstracts led to the exclusion of 295 articles. Final inclusion criteria—excluding animal cell experiments, non-blood sample studies, data extraction issues, reviews, and comments—resulted in 13 studies ( Gharesouran et al, 2019b ; Sayad et al, 2019 ; Shaker et al, 2019 ; Ghaiad et al, 2020 ; Senousy et al, 2020 ; Safa et al, 2021 ; Soltanmoradi et al, 2021 ; Akbari et al, 2022 ; Amiri et al, 2022 ; Attia et al, 2023 ; Ghafouri-Fard et al, 2023 ; Kamal et al, 2023 ; Kortam et al, 2023 ) qualifying for the meta-analysis. This process is detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%